Effective Leadership Styles in Project Management: A Literature Analysis of Their Impact on Project Success - Arfanaldy, Sehan Rifky (PT. Riset Press International, 2025)
Effective leadership is a key factor in the success of project management. This paper analyzes various leadership styles applied in project management through a literature review. The primary focus of this study is on transformational, transactional, and situational leadership styles and their impact on team performance and project outcomes. The findings suggest that selecting an appropriate leadership style depends significantly on the project context, team characteristics, and challenges faced. Transformational leadership is particularly effective in projects requiring innovation and high collaboration, while transactional leadership is more suited for structured projects with clear procedures. Additionally, situational leadership, which allows leaders to adjust their style based on the project's dynamic nature, is highly flexible and adaptive. Other contributing factors to project success include emotional intelligence, effective communication skills, and adapting to organizational culture and team diversity. These findings offer valuable insights for project management practitioners in selecting and developing leadership styles best suited to achieve optimal results in various project contexts.